PENGARUH HARGA, KUALITAS PRODUK, IKLAN DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING - Ayu Sekar Intan Nofita Kartika Sari; Heny Kurnianingsih (Jurnal AKTUAL, 2022)
Observations were made to find out whether purchasing decisions for Scarlett Whitening products were influenced by price, product quality, advertising, and variables celebrity endorsers. Technique purposive sampling chosen as a means to determine the sample. The selected respondents are 150. Price, product quality, advertising, celebrity endorser, and purchasing decisions are factors in the study. Data collected through questionnaires distributed to respondents. The techniques data review used include multiple linear regression, hypothesis testing, and testing the coefficient of determination. Test the data instrument and the classical assumption test as a data study tool. Research shows that purchasing decisions for Scarlett Whitening products are partially positively influenced by price but not significantly. Product quality, advertisements, and celebrity endorsers individually and simultaneously have a positive and significant effect on Scarlett Whitening products.